Evaluation of oxidative stress in endometriosis:A case-control study - Maryam Alizadeh; Soleiman Mahjoub; Seddigheh Esmaelzadeh; karimollah Hajian; Zahra Basirat; Maryam Ghasemy (Babol University of Medical Sciences, 2015)
Abstract Background: Recent studies have suggested that oxidative stress (OS) may have a contribution in the pathogenesis of endometriosis. However, the results of previous studies regarding OS in endometriosis are controversial. The objective of this study was to compare the serum levels of OS markers in endometriosis versus the control group. Methods: This case-control study was carried out on 30 women with endometriosis aged 20-38 from March 2011 to November 2013. These patients were admitted in Fatemeh Zahra Infertility and Reproductive Health Research Center, Babol, Iran. The serum samples of 40 women with same age were collected as the control group. The serum levels of malondialdehyde (MDA), carbonyl and iron were measured by photometric methods and compared between the patient and control groups using t-test. Also, we used ROC curve analysis to determine the discrimination ability of these markers. Results: Serum iron in endometriosis patients was significantly higher than control (p<0.0001). Area under ROC curve (AUC) for iron, MDA and carbonyl were 0.899, 0.648 and 0.530, respectively. Serum iron at cutoff value of 173.3 µg/dl exhibited high discrimination ability to recognize endometriosis from control. Conclusion: These findings indicate that the high level of serum iron may promote OS in patients with endometriosis. Also based on the ROC curve results, iron showed high discrimination ability to distinguish the patients with endometriosis from healthy subjects